PENDAMPINGAN PENYUSUNAN AKUNTANSI SEDERHANA PADA PELAKU UMKM DI KECAMATAN SEDAYU, YOGYAKARTA - Adelia Ardiyani; Hasim As'ari (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Micro, Small, and Medium Enterprises play a significant role in Indonesia’s economy. However, in practice, many business owners still do not manage their finances properly. Common issues include the absence of clear transaction records and the mixing of business and personal finances. This activity was conducted to assist MSME,  particularly laundry and photocopy businesses in Sedayu District, Yogyakarta, in preparing simple financial record. The method used was a participatory approach consisting of three stages: observation, socialization, and mentoring. The result show that prior to the assistance, business owners did not records their finances consistently & had difficulty understanding their financial condition clearly. After the program was implemented, there was an improvement in their understanding and skills in preparing simple bookkeeping, including recording cash inflows and outflows and separating personal and business finances. MSME owners were also able to prepare simple financial statements in the form of profit and loss calculations. Therefore, this mentoring activity had a positive impact on improving the quality of financial management among MSMEs, which can support business sustainability and growth.